2009
DOI: 10.32607/20758251-2009-1-3-99-101
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic Effects of Silver Nanoparticles on Mice in Vivo

Abstract: The toxic and genotoxic effects of silver nanoparticles were studied on injected mice (BALB/c line) in vivo. A water solution of silver nanoparticles (SNP) with particle sizes of 9±6 nm was obtained by means of the original method of biochemical synthesis. The effect of the SNP solution was compared to those of AOT (anionic surfactant used as SNP stabilizer) and silver nitrate (i.e. Ag+ ions) introduced as water solutions. In studies of the toxic effects, the death of mice was registered 12-24 hours after inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The aqueous solution of AgNPs with the particle size of 9 ± 6 nm was obtained by biochemical synthesis. The researchers compared nanosilver solution blended with sodium succinate diisooctyl sulfonate (anionic surfactant used as a nanosilver stabilizer) and silver nitrate (Ag + ), and found that the genetic toxicity of nanosilver solution is mainly produced by sodium succinate diisooctyl sulfonate (Ordzhonikidze, Ramaiyya, Egorova, & Rubanovich, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The aqueous solution of AgNPs with the particle size of 9 ± 6 nm was obtained by biochemical synthesis. The researchers compared nanosilver solution blended with sodium succinate diisooctyl sulfonate (anionic surfactant used as a nanosilver stabilizer) and silver nitrate (Ag + ), and found that the genetic toxicity of nanosilver solution is mainly produced by sodium succinate diisooctyl sulfonate (Ordzhonikidze, Ramaiyya, Egorova, & Rubanovich, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As such, there is a general consensus that smaller sized NPs produce higher reactivity and thus higher genotoxicity [62,63]. However, particle size is not the only factor that determines particle (geno-)toxicity.…”
Section: Genotoxicitymentioning
confidence: 99%
“…These results find indirect confirmation in [7], which describes an increasing level of DNA damages in the germ cells of rats when NS particles are administered intravenously with a diameter of 20 nm in doses of 5 and 10 mg/kg are administered intravenously. In the experiment on mice, a significant effect of NS in germ cells is revealed in the test of "anomaly of sperm heads" with the use of NS in a concentration of 170 mg/L [5]. Lower doses or concentrations of the substance are not studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, in general these papers are performed on models in vitro. In experiments in mice in vivo upon intraperitoneal or intravenous introduction, the cytogenetic effect of NS is established in bone-marrow cells [1,2] and blood reticulocytes [3] and the genotoxic effect is established in the Comet assay in bone marrow cells [2], liver [4], and spleen [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation